Désenchanter l’habitat spatial : environnements artificiels et mondes sans nature dans Aurora (K. S. Robinson), Shangri-La (M. Bablet) et Nos Temps contraires (G. Toriko) - Gatien Gambin (ReS Futurae, 2023)
The novel Aurora (Kim Stanley Robinson, 2015), the graphic novel Shangri-La (Mathieu Bablet, 2016) and the manga Nos temps contraires (Kimi o Shinasenai tame no Monogatari, Gin Toriko, 2020-2022 [2017-2021 in Japan]) form a corpus using space habitat as a narrative setting. These fictions are a part of narratives and iconography of space habitats defined notably by Gerard K. O’Neill’s essay The High Frontier (1977) illustrated by Donald E. Davis who presented space habitats as utopian places. Through a comparative study of these three fictions, we will show that they are less optimistic about these environments. They all present space habitats no longer as utopian places or as a plan B for the survival of humankind, but as limited environments from which we wish to escape. Aurora depicts an « astropastoral » environment (Brad Tabas, 2021) to interrogate the relationship between humanity and its habitat, whether natural or artificial. Shangri-La and Nos temps contraires depict worlds without nature to accentuate the dystopian setting of these stories. These three fictions also use the « limits aesthetic » (« esthétique des limites ») of the Anthropocene which has been theorized by Tommasio Guariento. It manifests in the corpus through two patterns: the Earth’s contemplation and the return to Earth. Thus, through the space habitat setting, this corpus mainly questions the humanity’s terrestrial condition in an era of ecological anxieties.